IgE responses to Ascaris and mite tropomyosins are risk factors for asthma (2015)
Background: The relationship between helminthiases and allergy is a matter of considerable interest and research. In the tropics, house dust mite exposure, a known risk factor for asthma, is frequently concurrent with helminth infections. It remains to be defined whether infection with the common roundworm Ascaris or its bystander immunological effects influence the prevalence and pathogenesis of asthma independently of mite sensitization. Objective: To investigate the relationship between the IgE responses to Ascaris and its purified allergens and the risk of asthma in a tropical country. Methods: A nested case-control study was performed in 356 subjects who reported current and past asthma symptoms (asthmatics) and 435 controls that had never experienced such symptoms. They were tested for serum levels of total IgE and specific IgE to Ascaris extract, Asc s 1 (ABA-1), Asc l 3 (tropomyosin) and GST (glutathione transferase). In addition, specific IgE to Dermatophagoides pteronyssinus, Blomia tropicalis and their tropomyosins Der p 10 and Blo t 10 was measured. Sensitization was defined as a positive specific IgE result to any extract or recombinant allergen. Results: Sensitization to Ascaris and D. pteronyssinus was independently associated with asthma after adjustment for age, gender, socio-economic stratum, city and other IgE levels (adjusted ORs: 2.17; 95% CI 1.37-3.42 and 2.46; 95% CI 1.54-3.92), respectively. There was also a significant association with sensitization to the highly allergenic and cross-reactive tropomyosins Asc l 3, Blo t 10 and Der p10 (aORs: 1.76; 95% CI 1.21-2.57, 1.64; 95% CI 1.14-2.35 and 1.51; 95% CI 1.02-2.24), respectively. Conclusion and Clinical Relevance: IgE responses to Ascaris are associated with asthma symptoms in a population living in the tropics. Sensitization to the cross-reactive Ascaris and mite tropomyosins partially underlies this finding. These results have potential relevance in asthma diagnosis and management. © 2015 John Wiley and Sons Ltd.